Diet self-management: A qualitative study of college students' experiences and perspectives - Zhou, Li; Chu, Yalin; Wei, Lai; Wang, Jing; Zhu, Xiaorong (Frontiers in Public Health, 2022)
Background Overweight and obesity among college students have become an emergent public health concern, which may be effectively prevented by diet self-management (DSM). The purpose of this explorative study was to explore college students' experiences and perspectives on diet self-management (DSM), as well as its influencing factors. Method Thirty-three college students were recruited from different universities in China. A qualitative method was used to conduct semi-structured interviews with audio recording to explore their DSM experience and factors that influence DSM. Data were analyzed using thematic analysis to develop themes related to DSM. Result In the perception of what "good DSM" means, three themes and ten subthemes were identified: characteristics of good DSM (including 5 subthemes: regularity, balanced diet, no picky eating, good eating habits, and scientificity), method of good DSM (including three subthemes: self-control, adjusting, and making plans), and content of good DSM (including two subthemes: nutrition management and safety management). The influencing factors of DSM can be categorized into four levels of themes and 34 subthemes: individual, family, school, and social levels. Conclusion The results of this qualitative research highlighted the complexity and multi-dimension of DSM and its influencing factors. Our findings may help to inform diverse and needs-based intervention approaches to improve DSM and promote healthy diet among college students so as to prevent overweight and obesity.